Effect of Acute Posttrauma Propranolol on PTSD Outcome and Physiological Responses During Script‐Driven Imagery - Hoge, Elizabeth A. (CNS Neurosci Ther, 2011)
Introduction: Animal and human research suggests that the development of posttraumatic stress disorder (PTSD) may involve the overconsolidation of memories of a traumatic experience. Previous studies have attempted to use pharmaceutical agents, especially the β‐adrenergic blocker propranolol, to reduce this overconsolidation. Aims: In this randomized, placebo‐controlled study of the efficacy of propranolol in reducing the development of PTSD, we optimized dosages and conducted both psychophysiological and clinical assessments 1 and 3 months after the traumatic event. Forty‐one emergency department patients who had experienced a qualifying acute psychological trauma were randomized to receive up to 240 mg/day of propranolol or placebo for 19 days. At 4 and 12 weeks post‐trauma, PTSD symptoms were assessed. One week later, participants engaged in script‐driven imagery of their traumatic event while psychophysiological responses were measured. Results: Physiological reactivity during script‐driven traumatic imagery, severity of PTSD symptoms, and the rate of the PTSD diagnostic outcome were not significantly different between the two groups. However, post hoc subgroup analyses showed that in participants with high drug adherence, at the 5‐week posttrauma assessment, physiological reactivity was significantly lower during script‐driven imagery in the propranolol than in the placebo subjects. Conclusions: The physiological results provide some limited support for a model of PTSD in which a traumatic conditioned response is reduced by posttrauma propranolol. However, the clinical results from this study do not support the preventive use of propranolol in the acute aftermath of a traumatic event.